About the features of the vision in the novel “The Idiot” by F.M. Dostoievski (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The proposed article considers the unique artistic experience of F. M. Dostoevsky in the sphere of visual perception of the world, a vision, which is spiritualized and humanized. The subject of the writer’s artistic vision is immediate thinking (idea). The novel «Idiot» is polyphonic, with a multitude of equal consciousnesses (voices), staying in unity and preserving their non-merging. There is also a multifaceted vision in this work. Excruciating and passionate, it reveals the hidden and the inmost in the spiritual, expressive mode. The whole world, refracted through the consciousness of each of the heroes, is subjective, but acquires meaning and significance in its unity.
Keywords: personalism; novel; polyphony; vision; peace; beauty